Correction: Komiyama et al. RNA-seq and Mitochondrial DNA Analysis of Adrenal Gland Metastatic Tissue in a Patient with Renal Cell Carcinoma. Biology 2022, 11, 589 - Tomoyoshi Komiyama; Hakushi Kim; Masayuki Tanaka; Sanae Isaki; Keiko Yokoyama; Akira Miyajima; Hiroyuki Kobayashi (Biology, 2022)
The authors would like to make the following correction to the published paper [...]